Studies in Growth Parameter and Pigment Contents in Endosulphan, EC- 35 Exposed Blue Green Alga (Anabena Cylindrica, L.) - Sabat, Goutam; Panigrahi, A.K.; Sahu, A.K.; Mohanty, Bijaya Kumar (International Journal of Applied Sciences and Biotechnology, 2014)
Anabaena cylindrica L, a blue green alga commonly found in rice fields was experimentally exposed with a board spectrum insecticide, Endosulphan, EC50 in laboratory conditions for varied days. The growth of alga in terms of increase in Absorbance, dry weight and pigments like Total chlorophyll, carotenoid and phaeophytin were estimated to study the toxic effect and the subsequent recovery from insecticide stress. The results obtained indicated decrease in all studied parameters with increase in exposure period and concentration. The highest concentration (3.25ml/L) and highest period (15 Days) severely affected the growth of alga and decreased pigment content. However, when the algae were allowed to grow in insecticide free environment for 15 days, they could able to recover fully from the toxic stress. DOI: http://dx.doi.org/10.3126/ijasbt.v2i3.10648 Int J Appl Sci Biotechnol, Vol. 2(3): 260-264